Penerapan Model Attention, Interest, Desire, Action (AIDA) pada Promosi Produk Hmns di Media Sosial Instagram - Abdurrafi Azhar; Christopher Yudha Erlangga (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
Product promotion via social media, especially Instagram, has become an effective strategy in reaching consumers widely and increasing audience engagement. This research aims to analyze the application of the AIDA (Attention, Interest, Desire, Action) model in the promotion of the perfume product